An Overview of the Antioxidant Effects of Ascorbic Acid and Alpha Lipoic Acid (in Liposomal Forms) as Adjuvant in Cancer Treatment - Mohamed Attia; Ebtessam Ahmed Essa; Randa Mohammed Zaki; Amal Ali Elkordy (MDPI AG, 2020)
Antioxidants are known to minimize oxidative stress by interacting with free radicals produced as a result of cell aerobic reactions. Oxidative stress has long been linked to many diseases, especially tumours. Therefore, antioxidants play a crucial role in the prevention or management of free radical-related diseases. However, most of these antioxidants have anticancer effects only if taken in large doses. Others show inadequate bioavailability due to their instability in the blood or having a hydrophilic nature that limits their permeation through the cell membrane. Therefore, entrapping antioxidants in liposomes may overcome these drawbacks as liposomes have the capability to accommodate both hydrophilic and hydrophobic compounds with a considerable stability. Additionally, liposomes have the capability to accumulate at the cancer tissue passively, due to their small sizes, with enhanced drug delivery. Additionally, liposomes can be engineered with targeting moieties to increase the delivery of chemotherapeutic agents to specific tumour cells with decreased accumulation in healthy tissues. Therefore, combined use of liposomes and antioxidants, with or without chemotherapeutic agents, is an attractive strategy to combat varies tumours. This mini review focuses on the liposomal delivery of selected antioxidants, namely ascorbic acid (AA) and alpha-lipoic acid (ALA). The contribution of these nanocarriers in enhancing the antioxidant effect of AA and ALA and consequently their anticancer potentials will be demonstrated.